Targeting Renal Proximal Tubule Cells in Obesity-Related Glomerulopathy - Muyao Ye; Ming Yang; Wenni Dai; Hao Li; Xun Zhou; Yinyin Chen; Liyu He (MDPI AG, 2023)
As a metabolic disorder, obesity can cause secondary kidney damage, which is called obesity-related glomerulopathy (ORG). As the incidence of obesity increases worldwide, so does the incidence of end-stage renal disease (ESRD) caused by ORGs. However, there is still a lack of effective strategies to prevent and delay the occurrence and development of ORG. Therefore, a deeper understanding and elaboration of the pathogenesis of ORG is conducive to the development of therapeutic drugs for ORG. Here, we review the characteristics of pathological lesions of ORG and describe the roles of lipid metabolism disorders and mitochondrial oxidative stress in the development of ORG. Finally, we summarize the current available drugs or compounds for the treatment of ORG and suggested that ameliorating renal lipid metabolism and mitochondrial function may be potential therapeutic targets for ORG.